UV Spectrophotometric Determination of Tolterodine Tartarate and Cefepime - Gowri Sankar, D.; Vamsi Krishna, M.; Kumar, D.V.S.P.; Latha, P.V.M. (Asian Journal of Chemistry, 2016)
UV spectrophotometric methods have been developed for the determination of tolterodine tartarate and cefepime in pure and pharmaceutical formulations. These methods obey Beer's law limits in the concentration range of 10–90 and 5–40 μg/mL, exhibiting maximum absorption at 280 and 240 nm respectively. These methods are extended to pharmaceutical preparations and there is no interference from any common pharmaceutical additives and diluents. The methods have been statistically evaluated and are found to be precise and accurate.